2000
DOI: 10.1159/000016622
|View full text |Cite
|
Sign up to set email alerts
|

Approximal Caries Depth Assessment with Storage Phosphor versus Film Radiography

Abstract: Objectives: To study whether caries–specific enhancement of storage phosphor images might improve the observer performance of approximal caries depth assessments compared with film radiography. Materials and Methods: 120 exposures were made of 120 extracted human teeth. To obtain geometrically identical images, Ektaspeed Plus films and storage phosphor plates were exposed simultaneously. The imaging plates were scanned in a Digora® scanner and the files transferred to a different platform for image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
0
30
2
2
Order By: Relevance
“…33 It was found that, in comparison with film (Ektaspeed Plus) images, PSP (Digora) images using a caries-specific enhancement feature significantly improved accuracy and reduced observer variability in assessing the depth of caries in the outer half of the enamel. 34 In the present study, only one of three observers had better Az values with PSP (Digora) than with film images, although the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 65%
“…33 It was found that, in comparison with film (Ektaspeed Plus) images, PSP (Digora) images using a caries-specific enhancement feature significantly improved accuracy and reduced observer variability in assessing the depth of caries in the outer half of the enamel. 34 In the present study, only one of three observers had better Az values with PSP (Digora) than with film images, although the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 65%
“…Svanaes et al 29 utilised a method of simultaneous exposure for the digital and conventional image receptors to obtain geometric accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In the most of studies (Velders et al, 1996;Svanaes et al, 2000;Wenzel, 2001;Khan et al, 2004;Young & Featherstone, 2005), the proximal carious lesion was evaluated by using the visual criterion. Although the visual criterion used was somewhat subjective, it represented the best clinical representation of a proximal carious lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographs are the most accurate diagnostic aid available for the detection of alveolar osseous abnormalities and dental disease progression (Russel & Pitts, 1993;Rothman, 1998). The development of digital radiography (radiovisiographs-RVG) has created new options in dentistry (Hedrick et al, 1994;Svanaes et al, 2000;Van der Stelt, 2005). However, imaging systems used in dentistry are largely limited to 2 dimensional (2-D) systems in including conventional-based radiography and digital radiography.…”
Section: Introductionmentioning
confidence: 99%